THE ROLE OF THE RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM IN THE DEVELOPMENT OF NEPHROGENIC ARTERIAL HYPERTENSION IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study investigates the functional activity of the renin-angiotensin-aldosterone system (RAAS) in secondary (nephrogenic) hypertension in children. Symptomatic hypertension refers to arterial hypertension (AH) that arises as a consequence of various pathological processes, where elevated blood pressure (BP) is one of the manifestations of an underlying disease. Symptomatic hypertension, which is involved in the regulation of BP, accounts for 3–25% of all hypertension cases. This paper examines the role of RAAS in the development of renoparenchymal and renovascular arterial hypertension (RVH).